Ricoeur's Philosophy of Subjectivity at the Face of Foucauldian Genealogy of Power - Direk, Zeynep (Sophia, 2025)
Ricoeur's reflection on subjectivity, developing in a hermeneutical direction, breaks up with Husserl's transcendental approach to subjectivity. He proposes in Oneself as Another (Ricoeur, 1992), a self-explication combining a non-transcendentalist phenomenological approach with hermeneutics and psychoanalysis. I argue that this new methodology can help Ricoeur to effectively respond to the challenge Foucault's thought presents to various phenomenological approaches to subjectivity. In the first part, I explain the reasons underlying Ricoeur's distancing himself from Husserl's Cartesian approach to subjectivity. In the second part, I focus on Foucault's genealogy of power underlying his rejection of the phenomenological approaches to subjectivity. In the last part, I discuss how Ricoeur conceives subjectivation via an eclectic approach that combines phenomenology with hermeneutics and psychoanalysis. Based on these three parts, I argue that Ricoeur's analysis can survive the Foucauldian critique.